Bleeding tendency and efficacy of anti-haemorrhagic treatments in patients with type 1 von Willebrand disease and increased von Willebrand factor clearance - Castaman, Giancarlo; Tosetto, Alberto; Federici, Augusto B.; Rodeghiero, Francesco (Thrombosis and Haemostasis, 2011)
Accelerated clearance of von Willebrand factor (VWF) has been recently identified as a major pathophysiologic mechanism inducing low VWF in some patients with von Willebrand disease (VWD). The frequency of bleeding and the best treatment of these patients have never been evaluated prospectively in large series of patients. It was the aim of the present study to prospectively evaluate clinical events of 60 heterozygous patients with VWD Vicenza (VWD-VI) carrying R1205H VWF mutation and 23 with C1130F mutation, both characterised by markedly increased VWF clearance. During 71 months of follow-up, 65% of patients with VWD-VI and 61% with C1130F required treatment. The rate of spontaneous bleeding requiring consultation/treatment was 7.5/100 patients-year in patients with C1130F mutation vs. 1.9/100 patients-year in those with R1205H (p=0.004). This difference persisted also by multivariate analysis adjusted for sex, age and blood group (hazard ratio [HR]=3.3 for C1130F, 95% confidence interval [CI] 1.16–9.27) and females were at greater risk of bleeding (HR=3, 95%CI 1.01–9.93) because of menorrhagia. Only 3/15 (20 %) women in fertile age with VWD-VI compared to 8/9 (89 %) with C1130F mutation required consultation/treatment for menorrhagia (iron supplementation, combined oral contraceptives, tranexamic acid). Almost all dental extractions, minor surgeries and deliveries occurring during follow-up were successfully managed with desmopressin. Major surgery required factor VIII/VWF concentrates, but a few cases benefited from desmopressin. In conclusion, similar to patients with type 1 VWD, also in patients with increased VWF clearance desmopressin maintains a major therapeutic role.
Keywords: von Willebrand factor; von Willebrand disease; inherited coagulation disorders